Measurement of the B0s→μ+μ− branching fraction and effective lifetime and search for B0→μ+μ−decays. - Aaij, R; Adeva, B; Adinolfi, M; Evans, T; Gandini, P; Gruberg Cazon, B; Hadavizadeh, T; Harnew, N; Hill, D; Jalocha, P; John, M; Jurik, N; et al. (American Physical Society, 2017)
A search for the rare decays B0s→μ+μ− and B0→μ+μ− is performed at the LHCb experiment using data collected in pp collisions corresponding to a total integrated luminosity of 4.4  fb−1. An excess of B0s→μ+μ− decays is observed with a significance of 7.8 standard deviations, representing the first observation of this decay in a single experiment. The branching fraction is measured to be B(B0s→μ+μ−)=(3.0±0.6+0.3−0.2)×10^−9, where the first uncertainty is statistical and the second systematic. The first measurement of the B0s→μ+μ− effective lifetime, τ(B0s→μ+μ−)=2.04±0.44±0.05  ps, is reported. No significant excess of B0→μ+μ− decays is found, and a 95% confidence level upper limit, B(B0→μ+μ−)<3.4×10^−10, is determined. All results are in agreement with the standard model expectations.